Original paperUrban-rural differences in the prevalence of atopic diseases in the general population in Lodz Province (Poland) - Kupryś-Lipińska, Izabela; Elgalal, Anna; Kuna, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Introduction: A dramatic increase in the prevalence of atopic diseases can be observed. The reasons for this phenomenon remain unclear. Aim: To compare the prevalence of atopic diseases in subjects living in the city centre and a rural area. Material and methods: The study was done on a randomly chosen group of inhabitants of Lodz province, aged 3 to 80 years, living in two different areas: the city centre and a rural area. Demographic data and the anamnesis were collected on the basis of standardised questionnaires. Additionally, skin prick tests and screening spirometries were performed. Results: The complete data from 482 subjects living in the city centre and 469 in the rural area were included in the analysis. Asthma prevalence in the city centre was estimated at 13.2% in adults and 18.4% in children compared to 4.2 and 6.0% respectively in the rural area. The prevalence of seasonal allergic rhinitis in the city centre was 13.2% in adults and 16.1% in children, in comparison to 10.1 and 6.7% in the rural area. Atopic dermatitis was diagnosed in 2.3% of adults and in 10.3% of children living in the city centre, compared to 0.3 and 11.9% in the rural area. The higher prevalence of asthma both in adults and children and seasonal allergic rhinitis in children, observed in the city centre, was statistically significant (p < 0.0001). The difference in atopic dermatitis reached statistical significance only in the group of adults, while the prevalence in the group of children did not differ between study regions. Conclusions: The study revealed a difference in the prevalence of atopic diseases between city and rural areas. The high prevalence of atopic dermatitis in the rural area may be a portent of an increase in other atopic diseases and the disappearance of the differences between city and rural areas.